- #1

discombobulated

- 41

- 0

f(x) = 6x

^{2}+ 12x + c where C is a constant.

a) Given f(x) =0 has equal roots, find the value of C.

so this what i did for this part:

b

^{2}- 4ac = 0 (formula for discriminant)

12

^{2}-4(6xC) =0

144-24c=0

6-C=0

c=6 (is that right?)

Now for the next part:

b) Hence, solve f(x) = 0

6x

^{2}+12x+6=0

(x=1)(6x+6)=0

x=-1 x= -6/6 = -1

I wasn't really sure what i was doing but i tried to work it out and this is what i did but I'm not sure if it's right. (i don't think it is!) Can somebody help please!